2022
DOI: 10.3390/nu14020302
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Mediterranean Diet among Children and Youth in the Mediterranean Region in Croatia: A Comparative Study

Abstract: The Mediterranean diet (MD) is considered one of the healthiest dietary patterns. The aim of this study was to assess MD adherence in children and youth living in the Mediterranean region in Croatia and evaluate the differences in adherence to the MD among different educational stages. In total, 2722 individuals aged 2 to 24 years were enrolled in this study. Subjects were divided into different groups according to the Croatian educational system. Mediterranean Diet Quality Index (KIDMED) was used to assess ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 50 publications
4
14
0
Order By: Relevance
“…However, there was significant variability in the samples analyzed, and direct comparisons could not be made between studies. Primary school students had a higher degree of adherence to MedDiet than secondary school students, which is in line with previous research [8,9,12,28]. This could be explained by adult supervision and control over children's diets, which is associated with following a healthy dietary pattern.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, there was significant variability in the samples analyzed, and direct comparisons could not be made between studies. Primary school students had a higher degree of adherence to MedDiet than secondary school students, which is in line with previous research [8,9,12,28]. This could be explained by adult supervision and control over children's diets, which is associated with following a healthy dietary pattern.…”
Section: Discussionsupporting
confidence: 88%
“…Optimal adherence to MedDiet was positively associated with meeting recommendations on physical activity and screen time. Optimal adherence to MedDiet was previously associated with physical activity practice [6,11,28,29], and it was inversely associated with screen time [6,11,[28][29][30]. High levels of physical fitness were associated with high adherence to MedDiet [28,29,31,32].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In this context, it is important to emphasize that, in order to be most effective, nutritional guidelines need to be developed according to several specific factors, such as local cultural, ethnic and traditional features, and geographic and socioeconomic components, as well as to the availability of specific local food products [ 9 ]. Among these features, the geographical location (i.e., a specific country, different areas in a country, such as seaside or mountainside or plains far from both, and specific latitude and climate, including climate changes, as well as the related social features) appears to be a crucial factor that may affect to a large extent the actual applicability of the Mediterranean diet or some of its principles as well as the actual adherence to it [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. An additional dynamic component affecting personal nutritional choices, also regarding adherence to the Mediterranean diet and its principles, is the individual life-long trajectory of food preference and nutrition habits and awareness, including feeding behavior aspects [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…A comparative study carried out among 2722 individuals aged 2 to 24 years living in Croatia showed low adherence to the MD over the entire sample [8]. Specifically, Matana et al, found that the prevalence rate of poor adherence to the increased with higher education stage, while the lowest rate was observed for the children enrolled in kindergartens [8].…”
mentioning
confidence: 99%